Strengthening Techniques for Deficient Beam-Column Joints Using FRP Composites (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Corner beam-column joints are critical and vulnerable elements in reinforced concrete moment-resisting frames due to their complex stress state and lack of confinement. This paper presents a comprehensive state-of-the-art review of strengthening techniques for these joints, with a principal focus on Fiber-Reinforced Polymer (FRP) composites, including externally bonded (EB-CFRP/GFRP) and near-surface mounted (NSM) systems. The analysis is extended to alternative methods such as Fabric-Reinforced Cementitious Matrix (FRCM) and high-performance concrete.Consolidated findings demonstrate that FRP interventions significantly enhance shear strength, energy dissipation, and ductility. Crucially, effective retrofitting shifts the failure mechanism from brittle joint shear to ductile beam hinging, upholding the "strong-column weak-beam" principle. The review critically identifies key influential factors: FRP configuration, area fraction, anchorage systems preventing debonding, and material type. A comparative analysis reveals that while FRPs offer superior strength-to-weight ratios, emerging materials like FRCM provide advantages in fire resistance and compatibility.This synthesis establishes that advanced composites are a superior alternative to conventional techniques for seismic upgrading. Finally, the review outlines essential research frontiers, including long-term durability, performance under bidirectional loading, and the development of standardized design codes for hybrid solutions, providing a critical reference for researchers and engineers.